2017
DOI: 10.1088/0253-6102/68/1/111
|View full text |Cite
|
Sign up to set email alerts
|

Modified Potential Around a Moving Test Charge in Strongly Coupled Dusty Plasma

Abstract: The theory of dynamical (wake) potential behind a moving test charge in a weakly coupled dusty plasma is extended to that including of strong interaction between dust grains. Such strong interaction is included in the dielectric response function by a generalized hydrodynamic (GH) fluid model. It is shown that the strong interaction between dusts including the lattice spacing correction has a significant effect on the wake potential in dusty plasma. This may be used to investigate basic features of phase trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
3
4
0
Order By: Relevance
“…The above dispersion relation includes the combined effects of external magnetic field, obliqueness, and strong correlation between dust grains. It extends the previous results [9,18] to the case of magnetized strongly coupled dusty plasma situations. Now let ω → ω + iδ in the dispersion relation and assume δ ω, we obtain the real and imaginary parts of the wave frequency as…”
Section: Hydrodynamics Regimesupporting
confidence: 87%
See 3 more Smart Citations
“…The above dispersion relation includes the combined effects of external magnetic field, obliqueness, and strong correlation between dust grains. It extends the previous results [9,18] to the case of magnetized strongly coupled dusty plasma situations. Now let ω → ω + iδ in the dispersion relation and assume δ ω, we obtain the real and imaginary parts of the wave frequency as…”
Section: Hydrodynamics Regimesupporting
confidence: 87%
“…The present article advances some previous studies [9,18,32,33] with the inclusion of an external magnetic field and the effect of the obliqueness of propagation in strongly coupled dusty plasma. It is shown that the external magnetic field as well as the obliqueness parameter can significantly modify the basic features of the wave propagation in an SCDMP system.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Since then, many investigations have been made to explain the wakefield potential distribution in different scenarios (Lemons et al, 2000;Ali, 2009;Ali, 2016). The dielectric response function and modified potential distribution around a test charge have also been studied in strongly coupled unmagnetized and magnetized dusty plasmas (Shahmansouri et al, 2017;Shahmansouri and Khodabakhshi, 2018;Shahmansouri, 2019).…”
Section: Introductionmentioning
confidence: 99%